Philosophy as a Way of Life: New Research Directions - Sharpe, Matthew (Philosophy as a Way of Life, 2025)
This book brings together contributions from leading scholars around the world on philosophy as a way of life (PWL), the research field opened up by the groundbreaking works of Pierre and Ilsetraut Hadot. The chapters examine how PWL opens up new perspectives on historical thinkers like Augustine, Alberti, and Mary Astell (part 1), examine the scope and dimensions of this growing research field, including in its comparative dimensions (part 2), and reflect upon PWL as a metaphilosophical paradigm (part 3). The collection as a whole, which closes with contributors reflecting on targeted questions, aims to chart the next research directions for PWL, 30 years after Pierre Hadot's classic study was translated into English.